Validation of a motion‐robust 2D sequential technique for quantification of hepatic proton density fat fraction during free breathing. Issue 6 (17th April 2018) - Pooler, B. Dustin; Hernando, Diego; Ruby, Jeannine A.; Ishii, Hiroshi; Shimakawa, Ann; Reeder, Scott B.
Abstract : Background: Current chemical‐shift‐encoded (CSE) MRI techniques for measuring hepatic proton density fat fraction (PDFF) are sensitive to motion artifacts. Purpose: Initial validation of a motion‐robust 2D‐sequential CSE‐MRI technique for quantification of hepatic PDFF. Study Type: Phantom study and prospective in vivo cohort. Population: Fifty adult patients (27 women, 23 men, mean age 57.2 years). Field Strength/Sequence: 3D, 2D‐interleaved, and 2D‐sequential CSE‐MRI acquisitions at 1.5T. Assessment: Three CSE‐MRI techniques (3D, 2D‐interleaved, 2D‐sequential) were performed in a PDFF phantom and in vivo. Reference standards were 3D CSE‐MRI PDFF measurements for the phantom study and single‐voxel MR spectroscopy hepatic PDFF measurements (MRS‐PDFF) in vivo. In vivo hepatic MRI‐PDFF measurements were performed during a single breath‐hold (BH) and free breathing (FB), and were repeated by a second reader for the FB 2D‐sequential sequence to assess interreader variability. Statistical Tests: Correlation plots to validate the 2D‐sequential CSE‐MRI against the phantom and in vivo reference standards. Bland–Altman analysis of FB versus BH CSE‐MRI acquisitions to evaluate robustness to motion. Bland–Altman analysis to assess interreader variability. Results: Phantom 2D‐sequential CSE‐MRI PDFF measurements demonstrated excellent agreement and correlation (R 2 > 0.99) with 3D CSE‐MRI. In vivo, the mean (±SD) hepatic PDFF was 8.8 ± 8.7% (range 0.6–28.5%). Compared with BH acquisitions, FB hepatic PDFF measurements demonstrated bias of +0.15% for 2D‐sequential compared with + 0.53% for 3D and +0.94% for 2D‐interleaved. 95% limits of agreement (LOA) were narrower for 2D‐sequential (±0.99%), compared with 3D (±3.72%) and 2D‐interleaved (±3.10%). All CSE‐MRI techniques had excellent correlation with MRS (R 2 > 0.97). The FB 2D‐sequential acquisition demonstrated little interreader variability, with mean bias of +0.07% and 95% LOA of ± 1.53%. Data Conclusion: This motion‐robust 2D‐sequential CSE‐MRI can accurately measure hepatic PDFF during free breathing in a patient population with a range of PDFF values of 0.6–28.5%, permitting accurate quantification of liver fat content without the need for suspended respiration. Level of Evidence: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;48:1578–1585